2021
DOI: 10.1001/jamaoto.2020.5031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parental Choice Predisposition for Tonsillectomy in Children

Abstract: The decision to proceed with tonsillectomy to treat pediatric obstructive sleep-disordered breathing (OSDB) often falls on individual families. Despite emphasis on shared decision-making between parents and surgeons about tonsillectomy for OSDB, the extent to which parents have already decided about surgery prior to the child's consultation is not known.OBJECTIVE To identify predictors of parent choice predisposition for surgical treatment of OSDB with tonsillectomy and describe its association with parent-cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…However, there is more susceptibility to sleep apnea before surgical removal of tonsils, which is also associated with increased scores on the post-consultation obstructive sleep disorders breathing and adenotonsillectomy knowledge score (OR, 4.07; 95% CI: 1.17 to 16.17) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is more susceptibility to sleep apnea before surgical removal of tonsils, which is also associated with increased scores on the post-consultation obstructive sleep disorders breathing and adenotonsillectomy knowledge score (OR, 4.07; 95% CI: 1.17 to 16.17) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings support themes in the qualitative study by Boss et al 18 in which parents commented on the importance of longitudinal, supportive relationships and communication with their pediatricians. Further, it has been suggested that the decision for surgery may be made in collaboration with their PCP, with whom they interact more frequently, even before discussions with the otolaryngologist 26 . PCPs have been described as gatekeepers of health care systems and therefore education in the primary care arena may improve equitable access to specialty care in SDB.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been suggested that the decision for surgery may be made in collaboration with their PCP, with whom they interact more frequently, even before discussions with the otolaryngologist. 26 PCPs have been described as gatekeepers of health care systems and therefore education in the primary care arena may improve equitable access to specialty care in SDB.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because parents with higher medical literacy are more receptive of medical interventions. 33 Given the low use of pediatric PSG nationally and the socioeconomic differences in use of sleep health care, we advocate for increased access to comprehensive, multidisciplinary diagnostics and treatment for pediatric OSAS. The responsibility for screening should be shared by all providers involved in the continuum of OSA care: primary care pediatricians, pulmonary and sleep specialists, otolaryngologists, dentists, and neurologists.…”
Section: Discussionmentioning
confidence: 99%
“…We found that children from higher education households were more likely to be evaluated for persistent sleep symptoms after TA and treated with CPAP. This may be because parents with higher medical literacy are more receptive of medical interventions 33 . Additionally, families with other members having previously undergone repeat PSG or using CPAP may be more willing to pursue postoperative interventions.…”
Section: Discussionmentioning
confidence: 99%